Expansion and Function of Repeat Domain Proteins During Stress and Development in Plants - Sharma, Manisha; Pandey, Girdhar K. (Frontiers in Plant Science, 2016)
The recurrent repeats having conserved stretches of amino acids exists across all domains of life. Subsequent repetition of single sequence motif and the number and length of the minimal repeating motifs are essential characteristics innate to these proteins. The proteins with tandem peptide repeats are essential for providing surface to mediate protein-protein interactions for fundamental biological functions. Plants are enriched in tandem repeat containing proteins typically distributed into various families. This has been assumed that the occurrence of multigene repeats families in plants enable them to cope up with adverse environmental conditions and allow them to rapidly acclimatize to these conditions. The evolution, structure and function of repeat proteins have been studied in all kingdoms of life. The presence of repeat proteins is particularly profuse in multicellular organisms in comparison to prokaryotes. The precipitous expansion of repeat proteins in plants is presumed to be through internal tandem duplications. Several repeat protein gene families have been identified in plants. Such as Armadillo (ARM), Ankyrin (ANK), HEAT, Kelch-like repeats, Tetratricopeptide (TPR), Leucine rich repeats (LRR), WD40, and Pentatricopeptide repeats (PPR). The structure and functions of these repeat proteins have been extensively studied in plants suggesting a critical role of these repeating peptides in plant cell physiology, stress and development. In this review, we illustrate the structural, functional and evolutionary prospects of prolific repeat proteins in plants.